Dimensions, standard scales, contributing authors, and items selected - Akshatha Rao (20605883) (2025)
Background This study investigates the mediating role of comfort (CMT), convenience (CNV), and aesthetics (AST) in the relationship between the enablers of an age-friendly built environment for walkability and outcomes such as increased physical activity level (IPL), increased socialization (ISL), and improved quality of life (IQL) in older adults. The research emphasizes the importance of creating age-friendly environments to support the well-being and quality of life of older adults, with implications for urban planners and policymakers to promote sustainable and inclusive design. Methods The research follows a positivist paradigm using a quantitative approach and survey strategy with a cross-sectional design. A sample of 333 older adults was selected using the convenience sampling technique, and data were gathered through a self-administered questionnaire. Results Findings from hypothesis testing indicate that, among the enablers, age-friendly urban design policies are the most significant construct, positively impacting all three mediating variables. aesthetics was found to have a significant positive effect on increased physical activity level and increased socialization, while comfort and convenience significantly influenced increased physical activity level and improved quality of life , respectively. Conclusion These results suggest implications for urban planners and policymakers to enhance the contribution of built environment for walkability toward increased physical activity level , increased socialization, and improved quality of life for older adults. The research offers valuable insights for academics and practitioners, emphasizing the importance of sustainable design while ensuring inclusivity to promote the well-being and quality of life of older adults.